Lectures on public economics - Atkinson, Anthony B.; Stiglitz, Joseph E. (Priceton: Princeton University Press, 2015)
"This classic introduction to public finance remains the best advanced-level textbook on the subject ever written. First published in 1980, Lectures on Public Economics still tops reading lists at many leading universities despite the fact that the book has been out of print for years. This new edition makes it readily available again to a new generation of students and practitioners in public economics.The lectures presented here examine the behavioral responses of households and firms to tax changes. Topics include the effects of taxation on labor supply, savings, risk-taking, the firm, debt, and economic growth. The book then delves into normative questions such as the design of tax systems, optimal taxation, public sector pricing, and public goods, including local public goods.Written by two of the world's preeminent economists, this edition of Lectures on Public Economics features a new introduction by Anthony Atkinson and Joseph Stiglitz that discusses the latest developments in the field and areas for future research. The definitive advanced-level textbook on public economics Examines the effects of taxation on households and firms Covers tax system design, optimal taxation, public sector pricing, and more Includes suggestions for further reading Additional resources available online "--
"Originally published in 1980 by McGraw-Hill"--Title page verso.
"With a new introduction by the authors"--Cover.
Includes bibliographical references(pages 481- 507) and indexes.
Keywords: Finance, Public; Welfare economics; BUSINESS & ECONOMICS / Economics / General; BUSINESS & ECONOMICS / Economics / Microeconomics; POLITICAL SCIENCE / Public Policy / Economic Policy; BUSINESS & ECONOMICS / International / Taxation